6+4(x-1)+8=

Simple and best practice solution for 6+4(x-1)+8= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+4(x-1)+8= equation:


Simplifying
6 + 4(x + -1) + 8 = 0

Reorder the terms:
6 + 4(-1 + x) + 8 = 0
6 + (-1 * 4 + x * 4) + 8 = 0
6 + (-4 + 4x) + 8 = 0

Reorder the terms:
6 + -4 + 8 + 4x = 0

Combine like terms: 6 + -4 = 2
2 + 8 + 4x = 0

Combine like terms: 2 + 8 = 10
10 + 4x = 0

Solving
10 + 4x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 4x = 0 + -10

Combine like terms: 10 + -10 = 0
0 + 4x = 0 + -10
4x = 0 + -10

Combine like terms: 0 + -10 = -10
4x = -10

Divide each side by '4'.
x = -2.5

Simplifying
x = -2.5

See similar equations:

| -12+8+(-2)= | | 5(x+4)-10= | | -2x-5=-2+1 | | 16p+14q= | | https://media.education2020.com/evresources/3108-05-05/mc018-1.jpg | | 3(x-1)+7= | | 9x-27=6x+12 | | -3+11=10y-13-19y | | (6x+2)-16=0 | | 8c-4/6c-3 | | 9x^2-24x-65=0 | | -7/3×n=-42 | | logx=2.45 | | -42-32r= | | 23+21z= | | B*8=96 | | -11v= | | 48=8-10n | | s^2+15s+20=0 | | 10x+5x-3x=120 | | 1+20xX=Y | | 4x-10x=14 | | .375x-13=-25 | | 0.66666666666x-6=9 | | 6-7=10y+4-9y | | (x*.055)+x=650 | | 8(c+10)20= | | -3(6p+2)-5p=63 | | 67=4(5+4b)-1 | | x^(1/3)/x^(1/4)*x^(-3/4) | | -13=4n-3+n | | 72=3(-5n-1) |

Equations solver categories